RISK ANALYSIS OF INJURY AND WORKING PRESSURE USING LAMP REPLACEMENT TOOLS - Hari Purnomo; Erni Yani; Ahmad Padhil (Journal of Industrial Engineering Management, 2020)
Lamp replacement is a work activity that is carried out manually using a chair or using a lamp replacement tool. The tool used to replace the lamp is deemed ineffective, which can lead to musculoskeletal complaints. Therefore it is necessary to redesign the replacement lamp to suit the needs of the user. The product proposed for lamp replacement design will be compared with existing tools to measure the level of work speed and stress. The analysis used to measure the level of work speed and stress is the Quick Exposure Check (QEC). The results showed that the percentage of exposure level for the old lamp replacement tool was 41% -59% so that further investigation was needed by redesigning the lamp replacement tool. Thus the use of replacement tools for old lamps when used is ineffective. The exposure level for a new lamp replacement is in the range of 20% -35%, meaning that it is accepted and recommended for use. In this case, the proposed lamp replacement tool is quite effective to use.